Venetoclax–Rituximab in Relapsed or Refractory Chronic Lymphocytic Leukemia - Seymour, John F; Kipps, Thomas J; Eichhorst, Barbara; Hillmen, Peter; D’Rozario, James; Assouline, Sarit; Owen, Carolyn; Gerecitano, John; Robak, Tadeusz; De la Serna, Javier; Jaeger, Ulrich; Cartron, Guillaume; et al. (The New England journal of medicine, 2018)
In a trial involving patients with relapsed or refractory chronic lymphocytic leukemia, the BCL2 inhibitor venetoclax in combination with rituximab resulted in a higher 2-year rate of progression-free survival than bendamustine in combination with rituximab (85% vs. 36%).